Quasi-equilibrium spectrum of free electrons forming at thermalization of a nonrelativistic beam in molecular gas; Modern Techniques and Technology (MTT' 2000) - Daneykin (Daneikin) Yu. V. Yuri Viktorovich (2000, 2000)
Title screen